Sexuality research in India: An update - Prakash, Om (Medknow Publications, 2010)
This review provides the available evidence on sexual dysfunctions in India. Most of the studies have concentrated on male sexual dysfunction and hardly a few have voiced the sexual problems in females. Erectile dysfunction (ED), premature ejaculation (PME) and combinations of ED and PME appear to be main dysfunctions reported in males. Dhat syndrome remains an important diagnosis reported in studies from North India. There is a paucity of literature on management issues with an emergent need to conduct systematic studies in this neglected area so that the concerns of these patients can be properly dealt with.